Current understanding of the molecular players involved in resistance to rice planthoppers. Issue 10 (12th June 2019) - Ling, Yang; Ang, Li; Weilin, Zhang
Abstract: Rice planthoppers are the most widespread and destructive pest of rice. Planthopper control depends greatly on the understanding of molecular players involved in resistance to planthoppers. This paper summarizes the recent progress in the understanding of some molecular players involved in resistance to planthoppers and the mechanisms involved. Recent researches showed that host‐plant resistance is the most promising sustainable approach for controlling planthoppers. Planthopper‐resistant varieties with a host‐plant resistance gene have been released for rice products. Integrated planthopper management is a proposed strategy to prolong the durability of host‐plant resistance. Bacillus spp. and their gene products or insect pathogenic fungi have great potential for application in the biological control of planthoppers. Enhancement of the activity of the natural enemies of planthoppers would be more cost‐effective and environmentally friendly. Various molecular processes regulate rice–planthopper interactions. Rice encounters planthopper attacks via transcription factors, secondary metabolites, and signaling networks in which phytohormones have central roles. Maintenance of cell wall integrity and lignification act as physical barriers. Indirect defenses of rice are regulated via chemical elicitors, honeydew‐associated elicitor, amendment with silicon and biochar, and salivary protein of BPH as elicitor or effector. Further research directions on planthopper control and rice defense against planthoppers are also put forward. © 2019 Society of Chemical Industry Abstract : Planthopper control require an understanding of the molecular players involved in resistance to planthopper. This article summarizes recent understanding of molecular players involved in resistance to planthoppers and the mechanisms involved.